2021
DOI: 10.1186/s43042-021-00145-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytochromes P450 3A4 and 2B6 gene polymorphisms on predisposition and prognosis of acute myeloid leukemia: an Egyptian case-control study

Abstract: Background It has been postulated that the interaction between environmental risk factors and genetic susceptibility is a possible cause for the development of acute myeloid leukemia (AML). Cytochrome P450 (CYP) detoxification enzymes are responsible for the elimination of oxidative stress. Genetic polymorphisms in these enzymes may cause AML due to enhanced accumulation of reactive oxygen species. To study the association between CYP3A4 (A290G) and CYP2B6 (G516T) gene polymorphisms and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…STATA software version 17 was applied to calculate the sample size and the findings of Botros et al when they examined the influence of CYPs polymorphisms on Egyptian patients with AML, as this is the first study to test CYPs polymorphisms in CLL patients from Egypt [ 22 ]. Analysis for a matched case-control study revealed that the sample size would be 47 participants per group (ratio 1:1), using a power of (80%) and an alpha error of (5%), and the chance of exposure in the control group would be 28%.…”
Section: Methodsmentioning
confidence: 99%
“…STATA software version 17 was applied to calculate the sample size and the findings of Botros et al when they examined the influence of CYPs polymorphisms on Egyptian patients with AML, as this is the first study to test CYPs polymorphisms in CLL patients from Egypt [ 22 ]. Analysis for a matched case-control study revealed that the sample size would be 47 participants per group (ratio 1:1), using a power of (80%) and an alpha error of (5%), and the chance of exposure in the control group would be 28%.…”
Section: Methodsmentioning
confidence: 99%
“…Pakakasma et al, on the other hand, found no significant difference in the distribution of CYP3A4(A290G) polymorphism between case and control [42]. This disparity may be explained by differences in acute leukemia risk factors between children and adults [35].…”
Section: Phase 1 Genetic Polymorphisms Most Frequently Associated Wit...mentioning
confidence: 95%
“…AML is a group of diseases characterized by clonal expansion of immature myeloid blasts, resulting in hematopoietic failure [34]. Through the inactivation of enzymatic activity, certain SNPs at the CYP genetic loci (CYP2D6, CYP1A1, CYP3A5, and CYP2E1) may be considered risk factors for many types of cancer and hematological malignancies, such as AML, ALL, and myelodysplastic syndromes (MDS) [35].…”
Section: Phase 1 Genetic Polymorphisms Most Frequently Associated Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…AML is a highly heterogenous and CD34 + CD38 -myeloid progenitor hematopoietic malignant disorder (da Cunha Vasconcelos et al, 2021). The etiology of this disease is virtually unknown, but the relationship between environmental risk and genetic susceptibility is believed to be a potential trigger for the formation of AML (Botros et al, 2021). The rate of occurrence rises considerably with the age at about 35/1 000 000 people.…”
Section: Introductionmentioning
confidence: 99%